Complejidad económica y crecimiento regional, evidencia de la economía Mexicana - Manuel Gómez-Zaldívar; Juan Carlos Chávez-Martín del Campo; Marco Tulio Mosqueda Chávez (Banco de México, 2016)
– In this study we use data on the productive structure of Mexican states to compute a measure of economic complexity for each, as well as for each economic activity conducted there. The results show that the states differ in terms of the economic activities in which they specialize and, therefore, also in terms of their economic complexity. As previous studies have shown, at an international level, there is evidence to affirm that the measure of economic complexity is relevant in explaining the observed economic disparities, since it is positively related to both the levels of wealth and the growth rates of the states.
Keywords: O10; O14; O47; 330; Diversity; Ubiquity; Complexity; Economic Growth